(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Every nation has its own historically formed traditions and customs, among them, the Uzbek people have a unique ethnographic history that has been formed over the years. Among such traditions, the weddings of the Uzbek people are the main rituals that have been practiced since ancient times until now.